Social media for business: Knowledge gathering through focus group session with business owners - Hassan, Shahizan; Shiratuddin, Norshuhada; Hashim, Nor Laily; Ab Salam, Sobihatun Nur; Sajat, Mohd Samsu (2012)
Despite its overwhelming popularity and widely recognized in business, studies on the trends and impact of social media in Malaysia, have yet to be widely recorded and published. As such, this study attempts to ascertain the usage of social media (SM) in business environment.Specifically, it aims to determine the trends and perceived impact of social media for business purposes in Malaysia.In order to accomplish this, the study follows four phases of methodology which are content analysis of current literature, focus group with Small Medium Enterprises (SMEs) on perceptions of users on the use of social media for business purposes, data findings and conclusion.The target population in this study is social media users in Malaysia, company owners/ employers (top management level), managers, executives,and employees. Simple random sampling procedure is employed to get the sample for the survey.